Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Skincare pada E-Commerce: Implementasi Sistem Informasi Manajemen - Adinda, Zahra; Azira, Mita (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to analyze the effect of management information systems on E-Commerce purchasing decisions for skincare products. This study uses the literature review method to analyze related articles from various relevant literature sources. This article reviews the factors that influence skin care purchasing decisions on E-Commerce. In this context, factors such as product quality, price, brand reputation, user reviews, promotions, user experience, product availability, return policy, and user experience are potential variables influencing consumer purchasing behaviour. The results showed that management information systems significantly influence purchasing decisions for skincare products in E-Commerce. This research provides practical implications for beauty industry players and e-commerce to improve marketing strategies, product management, and customer service. By understanding the significant factors in purchasing decisions, e-commerce can optimize management information systems to meet consumer expectations and increase the market share of skincare products online